THE EFFECT OF USING CANVA AND POUTON INTERACTIVE MEDIA ON THE SHORT STORY WRITING SKILLS OF EIGHTH-GRADE STUDENTS AT SMP NEGERI 7 BULUKUMBA - Andi Srirahayu; Haslinda Haslinda; Marwiah Marwiah (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to determine the effect of the application of Canva and Powtoon interactive media on the ability to write short stories for grade VIII students of SMP Negeri 7 Bulukumba. This study uses a quantitative approach with a quasi experiment design in the form of a nonequivalent control group design. The research subjects consisted of two classes, namely the experimental class that was treated using the interactive media Canva and Powtoon and the control class that used conventional learning methods. The data collection technique was carried out through a short story writing test in the form of a pretest and posttest. Data were analyzed using descriptive and inferential statistical tests with t-tests. The results showed that the significance value of the posttest t-test was 0.000 < 0.05, which means that there was a significant difference between the ability to write short stories for students in the experimental class and the control class. The average posttest score of the experimental class was 85.40 higher than the control class of 74.10. These findings show that the application of Canva and Powtoon interactive media is effective in improving students' short story writing skills. Therefore, Canva and Powtoon interactive media are recommended as alternative learning media in learning to write short stories at the junior high school level.